Perancangan Denim Wringer Memberikan Alternatif Hasil Dalam Proses Pencucian Denim Oleh Komunitas Denim Enthusiast.: The denim wringer design provides alternative results in the denim washing process by the Denim Enthusiast community. - Raihan Muhammad Fakhri; Maharani Permanasari (Penerbit Itenas, 2024)
This denim wringer research provides alternatives in the denim washing process by the Denim Enthusiast community. The denim industry has rapidly grown, followed by community developments with their routine events such as denim washing-pattern competitions resulted by the washing process. This denim wringer research uses Design Thinking methods, starting with direct observation to the Denim Enthusiast, followed by problem identification, analysis, design explorations, and prototypes that is tested directly by the community. The novelty of this research is a denim-wringer with an applicable design allowing the Denim Enthusiast community to operate in the washing process with ease, resulting a unique pattern or motifs.